Art Viewing Directives in Hospital Settings Effect on Mood. (April 2015) - Ho, Rainbow T. H.; Potash, Jordan S.; Fang, Fan; Rollins, Judy
Objective: The purpose of this study was to determine the effect viewing directives can have when encountering art in hospitals. A secondary objective of the study was to understand the responses of viewers to an art exhibit on the theme of medical student empathy toward patient pain and suffering. Background: Displaying art in hospitals has been credited with increasing well-being of patients, visitors, and staff. Generally, hospital curators have focused on the type of art to display (natural, symbolic, and abstract). This focus has neglected the possibility that in addition to the type of art, the way that viewers engage art may also be responsible for the healing effect. Methods: Participants (n = 97) were randomly allocated into one of the viewing directives: (1) reflecting on one artwork, (2) creating a drawing or poem in response to one artwork, or (3) no direction. Prior to looking at the art and immediately after, participants were administered the Brief Mood Introspection Scale (BMIS) and offered an opportunity to participate in an interview. Results: Pre–post results of the BMIS demonstrated that viewers who received directions achieved some therapeutic effect. Qualitative themes from the post-exhibit interviews identified that the empathy themed exhibit was well received, although there were differences among responses from patients, visitors, and staff. Conclusions: The results imply that hospitals may consider offering prompts to help viewers engage with art to enhance mood and exhibiting art that demonstrates empathy for patient suffering.